ENGAGEMENT OF CONVICTS TO PUBLICLY USEFUL LABOR IN THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
In this article, the involvement of convicts in socially useful work in the Republic of Uzbekistan was analyzed. The goal of penitentiary institutions in the country is not punishment, but re-upbringing. Therefore in order to train convicts in professions that are in demand on the labor market, improve their professional skills, effectively spend their free time and provide families with their work, production enterprises have been created in the institutions. And also the main goal of attracting convicts to work is to form in them the need to engage in socially useful activities. Labor relations of convicts are regulated by labor legislation and the Penitentiary Code of the Republic of Uzbekistan.